Phytochemical Characterization and Skin Cancer Inhibitory Potential of Ficus hispida Methanolic Extract: Insights from Molecular Docking and Cell-Based Assays: Phytochemicals in Ficus hispida Extract: Docking and Assays Reveal Skin Cancer Inhibition - Jatla, Murali Prakash; Kolli, Deepti (Iranian Journal of Pharmaceutical Sciences, 2026)
This study investigates the anticancer potential of Ficus hispida fruit extract, focusing on its phytochemical composition and molecular interactions with skin cancer targets. Fruits were collected from Jamia Salafiya Pharmacy College, and 500 g were subjected to Soxhlet extraction using methanol, yielding a concentrated ethyl acetate extract. LC-MS/MS analysis identified key bioactive compounds, including quercetin (m/z 302.33), kaempferol (m/z 284.26), gallic acid (m/z 169.14), lupeol (m/z 434.48), and β-sitosterol (m/z 414.58), confirming the extract’s chemical diversity. In-silico molecular docking showed that gallic acid exhibited notable binding affinities with skin cancer-related proteins: 1M17 (-6.3 kcal/mol), 4QTB (-5.4 kcal/mol), and 5MP8 (-5.6 kcal/mol). Hydrogen bonding, van der Waals interactions, and π-alkyl interactions were observed, particularly with residues Asp831, Arg-84, and Asn118, indicating the formation of stable ligand-protein complexes. Molecular dynamics (MD) simulations further validated stability, with low RMSD (2.0 Å) and compact radius of gyration (19.8 Å). MM-GBSA binding free energy analysis yielded a favorableΔG_bind of -58.61 kcal/mol for the gallic acid-1P7K complex. In vitro MTT assays revealed dose-dependent cytotoxicity of gallic acid against SKML skin cancer cells, with an IC50 value of 13.601±0.488 µg/mL. AO/EB staining confirmed effective induction of apoptosis in treated cells. These results collectively highlight the effectiveness of gallic acid from Ficus hispida as a promising candidate for skin cancer therapy, warranting further preclinical and clinical investigations for therapeutic development.